Keeping Pets from the Hadith Perspective - Abdul Kher; Muhammad Rizki Widiyanto; Moh Abdul Rahim (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss keeping pets from the perspective of the hadith. This study uses a qualitative approach by applying the analytical descriptive method. The formal object of this research is the hadith of the Prophet Muhammad regarding pets. The results of this research and discussion show that we are taught to love each other with fellow living beings, including pets. This study concludes that it is permissible to keep animals that are not prohibited by the Shari'a such as dogs and the importance of paying attention to the things that are needed by the pets they have, from eating, drinking, sheltering and so on.